2011
DOI: 10.1177/0013916511403802
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Designs for Patients of Different Ages

Abstract: The design of hospitals should consider the needs and preferences of the patients, but the preferences of adolescents have received little attention. This investigation analyzed adolescents' preferences for diverse hospital designs and compared them to those of the adults in charge of their care. Participants were 345 adolescents -88 of them hospitalized-76 parents, and 46 health professionals. They all assessed three pairs of photographs of different hospital settings. Quantitative analyses were performed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
4
2
Order By: Relevance
“…(Girl, 16 years; Translation)Here, Nanna details different colorful, thematically arranged rooms and compares the bedrooms to those in amusement parks and hotels. Despite previous research proposing that adolescents are opposed to child-like environments (Ullán et al, 2012), our older participants (12 years and above) stressed the importance of child-friendly and playful designs. In line with the descriptions of the lobby, bedroom features (“princess bed”) are contrasted with clinic elements (“sickbed”).…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…(Girl, 16 years; Translation)Here, Nanna details different colorful, thematically arranged rooms and compares the bedrooms to those in amusement parks and hotels. Despite previous research proposing that adolescents are opposed to child-like environments (Ullán et al, 2012), our older participants (12 years and above) stressed the importance of child-friendly and playful designs. In line with the descriptions of the lobby, bedroom features (“princess bed”) are contrasted with clinic elements (“sickbed”).…”
Section: Resultscontrasting
confidence: 94%
“…Our findings indicate that age differences in environmental preferences are not as clear-cut as previously presented (Peditto et al, 2020; Ullán et al, 2012), especially when adding the disability dimension to the analysis. We have shown that in a sample that is heterogeneous in age and ability, there is a great deal of consistency within the views on positive distraction and control.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Physical environments will therefore also differ in the extent that they provide an effective milieu for different types of social behaviors. For example, research on college dormitories, hospitals, and nursing homes has demonstrated that certain designs (e.g., suite vs. apartment layouts) influence the frequency of social interactions and subsequent feelings of belonging (Bronkema & Bowman, 2017;Devlin, Donovan, Nicolov, Nold, & Zandan, 2008;Dijkstra, Pieterse, & Pruyn, 2006;Ullán et al, 2012). Complexes that are designed to increase the frequency of chance encounters appear to enhance the social lives of occupants (Easterbrook & Vignoles, 2015).…”
Section: Designing Social Spacementioning
confidence: 99%
“…However, the opinion of the children has seldom been taken into account, since parents or guardians remain the main agents of information [14,15,16,17,18,19,20,21]. Nonetheless, there is an emerging trend whereby children and adolescents are directly asked about this issue [22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%